Breakthroughs in NiOx-HTMs towards stable, low-cost and efficient perovskite solar cells. (September 2018) - Sajid, Sajid; Elseman, Ahmed Mourtada; Huang, Hao; Ji, Jun; Dou, Shangyi; Jiang, Haoran; Liu, Xin; Wei, Dong; Cui, Peng; Li, Meicheng
Abstract: Although revolutionary progress in power conversion efficiencies (PCEs) of perovskite solar cells (PSCs) greater than 22% has accompanied significant advances in materials engineering, processing, and device architectures, the selection of proper hole transporting materials (HTMs) is still critical for high efficiency, low-cost and long-term stability. The PSCs community is actively investigating a group of HTMs for high efficiency and long-term stability with commercial viability. In this context, inorganic nickel oxide (NiOx )-HTMs possess the advantages of energetically favorable energy band positions, high hole mobility, superior chemical stability, and low cost manufacturing. Herein, we address the initial breakthroughs and recent progress in NiOx -HTMs for PSCs. In addition to synthetic routes and deposition techniques used for NiOx -HTMs in two major device architectures (p-i-n and n-i-p structure), the stability and cost-breakdown of PSCs are evaluated in details. Finally, future directions for further improvements on issues such as high efficiency, stability and low-cost of PSCs based on NiOx -HTMs are also provided. Graphical abstract: fx1 Highlights: The overall performance of perovskite solar cells based on NiOx -HTMs is reviewed. The effects of energetic landscape, high hole mobility, superior chemical stability and low-cost manufacturing are emphasized. Future research directions towards highly stable, low-cost and efficient PSCs are also suggested.